Perancangan Taman Vertikal Pada Dinding Underpass Simpang Tugu I Gusti Ngurah Rai - Pane, Radius; Sugianthara, Anak Agung Gede; Dharmadiatmika, I Made Agus (Jurnal Arsitektur Lansekap, 2024)
The increase in physical development in urban areas is in line with the increase in air pollution. The process of burning gas from the exhaust can pollute the air up to about 60% of other air pollutant factors. Air pollution that is commonly found in urban areas is Nitrogen Oxides (NOx). Nitrogen oxides (NOx) are chemical compounds of oxygen and nitrogen that are formed from combustion at high temperatures, especially the combustion of fuels that are responsible for the smog and brown clouds that cover large cities and produce poor air quality and cause serious health effects serious in humans. One way to overcome the problem of air pollution in urban areas with narrow land, is to plant a vertical garden model of road plants. Vertical garden is a landscaping business by utilizing land as much as possible, by utilizing the potential of vertical walls in the area so that the number of plants per unit area is more. The purpose of writing this paper is to see the potential application of the concept of vertical gardens on the underpass wall by optimizing the potential and overcoming obstacles in the path of the Simpang Tugu I Gusti Ngurah Rai underpass. The research method used is a survey method with data collection techniques through observation, interviews, and literature studies. The results showed that the underpass wall can be installed with a vertical garden with a structural truss method that is attached to the underpass wall and using a drip irrigation system controlled by a timer for watering and fertilizing. And the results of the vegetation design using shrubs that are able to neutralize nitrogen oxides (NOx), namely Es lilin hijau (Chlorophytum bichetii), Kriminil hijau (Alternanthera ficoida) and Taiwan beauty (Cuphea hyssophylla). For the design of the vertical garden planting pattern, it will follow the stylized form of the Mas-Mas Keketusan Ornament.